2016
DOI: 10.12659/msm.897315
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Isothiocyanate Inhibits the Proliferation of Renal Carcinoma Cell Line GRC-1 by Inducing an Imbalance Between Bcl2 and Bax

Abstract: BackgroundBecause of the insensitivity of renal cell carcinoma (RCC) to both chemotherapy and radiotherapy, surgery remains the primary approach for anticancer treatment. However, patients who do not receive timely diagnoses may not be suitable for surgery, especially in the late phase of tumor development. Thus, the discovery of novel effective treatment is of great importance. Allyl isothiocyanate (AITC) can inhibit the proliferation and induce apoptosis in many cancer cells. In this paper, we report on an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…DNA methylation is a proven mechanism of BNIP3 downregulation in tumors. In a previous study, Murai and coworkers demonstrated that BNIP3 was methylated in 65.6% of colorectal cancer tissues, although it was not methylated in adjacent normal tissue samples ( 15 , 40 ). Similarly, Cleven et al ( 41 ) also demonstrated the occurrence of BNIP3 methylation in 52.8% of colorectal cancer cells, and that treatment with 5-aza-C restored the expression of BNIP3 and led to increased apoptosis and autophagy, with enhanced sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…DNA methylation is a proven mechanism of BNIP3 downregulation in tumors. In a previous study, Murai and coworkers demonstrated that BNIP3 was methylated in 65.6% of colorectal cancer tissues, although it was not methylated in adjacent normal tissue samples ( 15 , 40 ). Similarly, Cleven et al ( 41 ) also demonstrated the occurrence of BNIP3 methylation in 52.8% of colorectal cancer cells, and that treatment with 5-aza-C restored the expression of BNIP3 and led to increased apoptosis and autophagy, with enhanced sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Following cell dissociation and propagation, the 786-O, A498, ACHN, and GRC-1-1 cell lines were cultured (37°C) and grown in Roswell Park Memorial Institute (RPMI) medium using 1640 complete medium (Gibco ® ; Thermo Fisher Scientific, Inc., Waltham, MA, USA). The GRC-1 RCC line was established at the Institute of Urology, Peking University (Beijing, China), was first reported by Ding et al ( 14 ), and has been subsequently used in numerous studies ( 15 , 16 ). PC3 and Du145 cells were cultured (37°C) in Dulbecco’s modified Eagle’s medium (DMEM) complete medium (Gibco ® ; Thermo Fisher Scientific, Inc.), whereas HK-2 cells were cultured (37°C) in F-12 Complete™ medium (Gibco ® ; Thermo Fisher Scientific, Inc.) in microcentrifuge tubes (Eppendorf, Stevenage, UK) in a humidified incubator in an atmosphere of 5% CO 2 and 95% air.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, blocking Ca 2+ -based ER stress signals and ROS formation significantly attenuated AITC-induced HT-29 cell apoptosis. The effective cytotoxic actions of AITC on multiple human cancer cell lines are well documented (12,(16)(17)(18)(19)(20)(21); however, the detailed mechanisms involved in the cytotoxic effects of AITC in HT-29 cells remain elusive. Our results indicated that AITC inhibited HT-29 cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Human RCC, 786-0 and GRC-1 ( 7 ), and normal human kidney cells, HK-2 were purchased from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China). All of the cells were maintained in DMEM (Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10% FBS (Gibco; Thermo Fisher Scientific, Inc.) and incubated at 37°C in humidified air with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%